…Wallhausen. Once more on the denarius with the legend +UVALHVZE - Chabrzyk, Piotr (Acta Archaeologica Lodziensia, 2021)
The topic of this paper is the issue of a possible place of coining the cross denarii with the legend +UVALHVZE, associated with the town of Wallhausen on the Helme river. Chronology of the coin production is touched upon, as well as the direction of its inflow based on the spread of hoards containing that piece. In the early 1930’s a heated debate regarding those coins took place between two distinguished numismatist of that time – Julius Menadier and Marian Gumowski. The German scholar dated the coin to the beginning of the 11th century and connected it with Mathilde the Abbess of Quedlinburg. In the legend he saw the name of a small town – Wallhausen on the Helme, where the Emperors palace was located. Gumowski on the other hand linked the coins with the count palatine Sieciech and dated it close to the year 1080. The analysis of hoards and a single find from the Schulzenwerder island allowed for the narrowing of the coins chronology to the years 1060-1070. It was Menadier who was probably right in linking it with the town of Wallhausen as we lack other interpretations of the legend. It could have been minted by Eberhard the Bishop of Naumburg (1045-1079), or by the Archbishopric of Magdeburg which was the superior of Naumburg. The coins had been minted with one obverse die, which with the passage of time was repaired and two reverse dies.